2012
DOI: 10.1364/boe.3.003127
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative OCT angiography of optic nerve head blood flow

Abstract: Optic nerve head (ONH) blood flow may be associated with glaucoma development. A reliable method to quantify ONH blood flow could provide insight into the vascular component of glaucoma pathophysiology. Using ultrahigh-speed optical coherence tomography (OCT), we developed a new 3D angiography algorithm called split-spectrum amplitude-decorrelation angiography (SSADA) for imaging ONH microcirculation. In this study, a method to quantify SSADA results was developed and used to detect ONH perfusion changes in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
328
2
10

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 435 publications
(355 citation statements)
references
References 34 publications
10
328
2
10
Order By: Relevance
“…Motivated by the fact that pixels from static tissue yield small decorrelation values while pixels from the faster moving tissue yield high decorrelation values [7][8], we propose to compute decorrelations from overlapping scans and use the en face decorrelation image. This implies that the proposed method is not suitable to data without any overlapping scan.…”
Section: Motion Detectionmentioning
confidence: 99%
“…Motivated by the fact that pixels from static tissue yield small decorrelation values while pixels from the faster moving tissue yield high decorrelation values [7][8], we propose to compute decorrelations from overlapping scans and use the en face decorrelation image. This implies that the proposed method is not suitable to data without any overlapping scan.…”
Section: Motion Detectionmentioning
confidence: 99%
“…In [6], the authors postulated that optic nerve head (ONH) blood flow may be associated with glaucoma development and proposed the use of Split-spectrum amplitude-decorrelation angiography (SSADA) method [7] together with flow index and vessel density for glaucoma detection. The split-spectrum amplitude-decorrelation angiography method [7] detects motion of blood flow as decorrelation of signals' amplitude between multiple sequential OCT B-scans taken at the same cross-section to construct a map of blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…Using OCT-A the vascular density in the optic nerve head (ONH) and peripapillary area was measured. [19][20][21] The authors found reduced ONH blood vessel density that was associated with structural and functional glaucomatous damage. [22][23][24][25] The purpose of the present study was to assess vascularity of the macular area in patients with glaucoma by means of OCT-A.…”
mentioning
confidence: 97%
“…A new 3D angiography algorithm (split-spectrum amplitude-decorrelation angiography, (SSADA)) was developed for imaging retinal microcirculation. 19 This method is based on ultrahigh-speed optical coherence tomography (OCT), and was called OCT-angiography (OCT-A). Using OCT-A the vascular density in the optic nerve head (ONH) and peripapillary area was measured.…”
mentioning
confidence: 99%
See 1 more Smart Citation